Students’ satisfaction with general practitioners’ feedback to their reflective writing: a randomized controlled trial - Kiss, Alexander; Steiner, Claudia; Grossman, Paul; Langewitz, Wolf; Tschudi, Peter; Kiessling, Claudia (Canadian Medical Education Journal, 2017)
Background: Reflective Writing (RW) is increasingly being implemented in medical education. Feedback to students’ reflective writing (RW) is essential, but resources for individualized feedback often lack. We aimed to determine whether general practitioners (GPs) teaching students clinical skills could also provide feedback to RW and whether an instruction letter specific to RW feedback increases students’ satisfaction. Methods: GPs were randomized to the two study arms using block randomization. GPs in both groups received an instruction letter on giving students feedback on clinical skills. Additionally, intervention group GPs received specific instructions on providing feedback to students’ RW. Students completed satisfaction questionnaires on feedback received on clinical skills and RW. T-tests were employed for all statistical analysis to compare groups. Results: Eighty-three out of 134 physicians participated: 38 were randomized to the control, 45 to the intervention group. Students were very satisfied with the feedback on RW and clinical skills regardless of tutors’ group allocation. A specific instruction letter had no additional effect on students’ satisfaction. Conclusion: Based on student satisfaction, GPs who give students feedback on clinical skills are also well suited to provide feedback on RW. This approach can facilitate the introduction of mandatory RW into the regular medical curriculum.